Probiotic Bifidobacteria in Managing Periodontal Disease: A Systematic Review - Victor Haruo Matsubara; Kausar Sadia Fakhruddin; Hien Ngo; Lakshman P. Samaranayake (Elsevier, 2023)
ABSTRACT: Although various probiotic organisms have been evaluated for their utility in the management of periodontitis, their strain-specific mechanisms of action are still unclear. We aimed to systematically review the effect of bifidobacterial probiotics on periodontopathogens and host immune responses in periodontal diseases. An electronic search of articles published until June 2022 in Medline, PubMed, Web of Science, and Cochrane Library databases was performed. Randomised controlled trials (RCTs) and in vitro and animal studies were assessed, and the data regarding antimicrobial properties, immunomodulation, and clinical outcomes were analysed. A total of 304 studies were screened, but only 3 RCTs and 6 animal and in vitro studies met the inclusion criteria. The use of different strains of bifidobacteria led to (1) a reduction of key players of the red complex periodontopathogens; (2) reduced levels of pro-inflammatory cytokines (eg, interleukin [IL]1-β and IL-8) and higher levels of anti-inflammatory cytokines (IL-10); (3) enhanced levels of osteoprotegerin and reduced levels of receptor activator of nuclear factor kappa-B ligand; and (4) a reduction of the dental plaque, bleeding on probing, alveolar bone loss, and clinical attachment loss. Bifidobacterial probiotic adjuvant supplementation, especially with Bifidobacterium animalis subspecies lactis, appears to help improve clinical periodontal parameters and develop a healthy plaque microbiome through microbiological and immunomodulatory pathways. Further human and animal studies are warranted prior to the therapeutic use of bifidobacteria in the routine management of periodontal infections.